PENGARUH NILAI PELAYANAN TERHADAP CITRA PERUSAHAAN DI MATA KLAIMEN PT JASA RAHARJA (PERSERO) KANTOR PERWAKILAN BOJONEGORO - Jihan Jihan; Ari Kuntardina (Sekolah Tinggi Ilmu Ekonomi YPPI Rembang, 2020)
PT. Jasa Raharja is in charge of providing compensation for road traffic accident victims. Thus, people who have an accident will feel helped by the existence of PT. Jasa Raharja. The research objective was to test and analyze the effect of PRIME PT Jasa Raharja (Persero) Bojonegoro Representative Office on company image in the eyes of beneficiary claimants. This research is a survey research. The sampling technique used was Proportionate Random Sampling. Data collection by questionnaire to 50 claiment PT Jasa Raharja in Bojonegoro Regency. Data analysis used Multiple Linear Regression Analysis. The results of data analysis show that the value of Proactive, Friendly, and Easy partially has a significant and positive effect on company image, while the values of sincerity and empathy partially do not have a significant effect on the corporate image of PT Jasa Raharja (Persero) Bojonegoro Representative Office. Meanwhile, the five PRIME values (proactive, friendly, sincere, easy, and empathetic) together have a significant effect on the company's image in the eyes of PT Jasa Raharja's claimants, Bojonegoro Representative Office.